2018
DOI: 10.3389/fpsyg.2018.00922
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Values of Early Parental Loss and Psychopathological Risk for Physical Problems in Early Adolescents

Abstract: Background: Several studies have suggested that the early loss of parents is a potentially traumatic experience, exposing adolescents to a higher risk for the onset of psychopathological symptoms. Furthermore, research has shown an association between the loss of a parent in childhood and subsequent physical illnesses, but much less attention has been given to the predictive role of loss in the development of physical illness in adolescence.Methods: From a larger normative sample, we selected 418 early adolesc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 109 publications
(118 reference statements)
2
28
0
2
Order By: Relevance
“…They can also cause feelings of embarrassment, selfawareness and may interfere with school attendance and peer relationships. Previous studies have shown that depression is often associated with physical comorbidities [64]. Our study findings corroborates the need to screen children with physical co-morbidities for the presence of symptoms of depression.…”
Section: Discussionsupporting
confidence: 89%
“…They can also cause feelings of embarrassment, selfawareness and may interfere with school attendance and peer relationships. Previous studies have shown that depression is often associated with physical comorbidities [64]. Our study findings corroborates the need to screen children with physical co-morbidities for the presence of symptoms of depression.…”
Section: Discussionsupporting
confidence: 89%
“…Our results regarding the links of family effects with psychopathological presentations (as measured with the SCL-90-R) are aligning with past evidence involving young individuals [ 7 , 15 22 , 74 ]. Nevertheless, the present work methodologically expands past literature in at least two ways: a) the examination of a large and normative cohort of Greek high school students and; b) the concurrent assessment of all the nine symptom specific dimensions of the SCL-90-R and the five major family aspects, as reflected by FACES-IV.…”
Section: Discussionsupporting
confidence: 90%
“…The death of a parent is highly traumatic for dependent children; without appropriate support it can have long-term effects on schooling, relationships, independence and emotional well-being 1–5. The number of children who experience the death of a parent is significant.…”
Section: Introductionmentioning
confidence: 99%